(Table 1, page 73) Chemical analyses of four micronodule types, differing in colour and structure, from the summit of Mount Palinuro, Mediterranean Sea - Robert B Kidd; H Armannson (PANGAEA, 1979)
A gravelly sand deposit at 103 m depth on the summit region of Mount Palinuro, a seamount approximately 100 km off the Italian west coast, is made up of a mixture of manganese and iron micronodules with shallow water shell debris. The manganese-rich concretions have very high Mn:Fe ratios, are deficient in minor elements and todorokite is their principal manganese oxide phase. The iron-rich concretions are almost entirely composed of smectite. The high degree of partition of manganese and iron and the mineralogical variation suggest that the micronodules probably have a hydrothermal origin. The associated shell debris contains no fossil component showing that Mount Palinuro has been volcanically active in historically recent times. This places constraints on models for the tectonism of the southern Tyrrhenian Sea.
Supplement to: Kidd, RB; Armannson, H (1979): Manganese and iron micronodules from a volcanic seamount in the Tyrrhenian Sea. Journal of the Geological Society, 136(1), 71-76, https://doi.org/10.1144/gsjgs.136.1.0071